Erectile Dysfunction and Obstructive Sleep Apnea: A Review - Gu, Yiwei; Wu, ChangJing; Qin, Feng; Yuan, Jiuhong (Frontiers in Psychiatry, 2022)
Erectile dysfunction (ED) is a disease with a wide scope of etiologies. Obstructive sleep apnea (OSA) is considered one of the risk factors for ED and is less studied. Increasing evidence shows an association between OSA and ED. This study provides an updated review of the relationship between ED and OSA and the possible physiological mechanisms of ED in OSA patients based on the current evidence. In clinical interviews, patients with ED may benefit from a sleep evaluation. However, further clinical investigations and more basic researches are needed to illustrate the relationship between ED and OSA.